Processing of personal data in connection with self-employment - Rzymowski, Jakub (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The chapter concerns the processing of personal data in connection with self-employment and in connection with cooperation between a self-employed person and another entrepreneur. In this chapter, we consider what roles a self-employed person can assume from the point of view of the GDPR. Much space is devoted to the self-employed person as a processor.